2013
DOI: 10.5897/ajfs12.037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and determination of the factors affecting anti-listerial bacteriocins from Lactobacillus plantarum and Pediococcus pentosaceus isolated from dairy milk products

Abstract: Lactobacillus plantarum and Pediococcus pentosaceus strains isolated from dairy milk products, produced bacteriocins that displayed a wide spectrum of antimicrobial activity against Listeria ivanovii and food spoilage microorganisms. The two bacteriocins were thermally stable over a wide temperature range up to 100°C for 15 min and retained their activity at pH 2.0 to 6.0. Full bacteriocins activity were stable after three months of storage at 4 and -20°C, for 75 min of exposure to UV light, bacteriocin produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…A previous study indicated that the activity might be linked to the intensification of bacteriocin solubility or due to the ability of acids to pass beyond the target cell membranes acidifying the cytoplasm and increasing its permeability, thus leading to inhibition of pathogen growth ( 16 ). The same trend was found by Fatima and Mebrouk ( 30 ) when they studied the inhibitory activity of bacteriocin produced by L. plantarum and Pediococcus pentaceus . Inconsistent with these results, the inhibitory activity of bacteriocin produced by L. lactis subsp.…”
Section: Resultssupporting
confidence: 83%
“…A previous study indicated that the activity might be linked to the intensification of bacteriocin solubility or due to the ability of acids to pass beyond the target cell membranes acidifying the cytoplasm and increasing its permeability, thus leading to inhibition of pathogen growth ( 16 ). The same trend was found by Fatima and Mebrouk ( 30 ) when they studied the inhibitory activity of bacteriocin produced by L. plantarum and Pediococcus pentaceus . Inconsistent with these results, the inhibitory activity of bacteriocin produced by L. lactis subsp.…”
Section: Resultssupporting
confidence: 83%
“…plantarum (BLp) was quite active even passing through high temperature and pressure during sterilisation, indicating it is a heat-stable protein. Abo-Amer and Fatima and Mebrouk have reported similar observations in different studies [ 18 , 19 ], emphasising the usefulness of L . plantarum bacteriocin in food preservation procedures due to its high-temperature tolerance.…”
Section: Resultssupporting
confidence: 62%
“…The purified sample lost its bacteriocin like activity (no zone of inhibition) at pH 2 and 12 but the treatment at pH 4, 7 and 10 did not affect the activity of the sample. The bacteriocin from Lactobacillus plantarum and Pediococcus pentosaceus was also active at the pH range of 2 to 6 (Fatima and Mebrouk, 2013). The purified bacteriocin retained its activity after treating to autoclave temperature but the activity was comparatively lesser than the activity of the bacteriocin maintained at room temperature.…”
Section: Resultsmentioning
confidence: 96%